The Hantzsch Pyrrole Synthesis: Non-conventional Variations and Applications of a Neglected Classical Reaction - Leonardi, Marco; Estévez, Verónica; Villacampa, Mercedes; Menéndez, J. Carlos (Synthesis, 2019)
Pyrrole is one of the most important one-ring heterocycles because of its widespread presence in natural products and unnatural bioactive compounds and drugs in clinical use. The preparation of pyrroles by reaction between primary amines, β-dicarbonyl compounds, and α-halo ketones, known as the Hantzsch pyrrole synthesis, is reviewed here for the first time. In spite of its age and its named reaction status, this method has received little attention in the literature. Recent work involving the use of non-conventional conditions has rejuvenated this classical reaction and this is emphasized in this review. Some applications of the Hantzsch reaction in target-oriented synthesis are also discussed.1 Introduction2 The Conventional Hantzsch Pyrrole Synthesis3 Hantzsch Pyrrole Synthesis under Non-conventional Conditions4 Applications of the Hantzsch Pyrrole Synthesis5 Conclusions
Keywords: pyrrole; green chemistry; solid-phase synthesis; sonochemistry; flow synthesis; photoredox catalysis; mechanochemical synthesis